Low Voltage Ride-Through of Doubly Fed Induction Machine using Direct Torque Control Strategy - G. Venu Madhav; Y. P. Obulesu (Institute of Advanced Engineering and Science, 2013)
The wind turbines based Doubly Fed Induction Machine (DFIM) not able to support the voltage and the frequency of the grid during and immediately following the grid failure. This would cause major problems for the systems stability, but the turbines should stay connected to the grid in case of a failure. This can be achieved by using crowbar protection in particularly during voltage dips. When low depth voltage dips occur, the necessity of crowbar proctection can be eliminated by using proposed Direct Torque Control (DTC), with a proper rotor flux generation strategy, by which during the fault it will be possible to maintain the machine connected to grid, generating power from the wind, reducing the stator and rotor over currents, eliminating the torque oscillations that normally produce such voltage dips and fast dynamic response accompanies the overall control of the wind turbine.DOI: http://dx.doi.org/10.11591/ijpeds.v3i1.1733